Primary paraganglioma-like dermal melanocytic tumor in a dog - Ramírez-Hernández, Cecilia; Castro-Valtierra, Carlos Ernesto; García-Valle, Jorge Luis; García-Márquez, Luis Jorge; Ramírez-Romero, Rafael (Brazilian Journal of Veterinary Pathology, 2024)
Melanocyte-derived tumors are common in humans and dogs. Their natural presentation in dogs is comparable to that of humans. Therefore, the dog has been proposed as a model in comparative pathology. Melanocyte-derived tumors are highly heterogeneous neoplasms considered the great mimickers because, in rare presentations in humans, their histopathology may include other distinct, unexpected tissue images. The term paraganglioma-like dermal melanocytic tumor refers to a rare neoplasm with a neuroendocrine (paraganglioma) pattern documented in human beings. Twelve cases have been registered to date. A case with these characteristics is herein described in a dog’s skin. To the best of the authors’ knowledge, this is the first case of a dermal melanocytic tumor with the paraganglioma-like pattern described in veterinary pathology.